Scanning and Transmission Electron-Microscopic Studies on the Lingual Tonsil of the Buffalo (Bubalus bubalis) - Girgiri, Ibrahim Alhaji; Kumar, Pawan (Journal of Buffalo Science, 2020)
The present study examined lingual tonsil of six buffaloes of the local mixed breed by scanning and transmission electron-microscopy to elucidate their ultrastructural features. The lingual tonsil presented folded mucosa having longitudinally oriented folds which were separated by grooves. The surface mucosa showed a squamous arrangement of cells which delineated from the adjacent cells. The surface of these cells at a higher magnification presented the microplicae of different arrangements which were mainly of closed pattern type and resembled fingerprints of humans. The luminal openings of glandular ducts on the free surface presented varying shapes. The transmission electron-microscopy described ultrastructural details of the different strata of the stratified squamous keratinised, non-keratinised and reticular epithelia. The propria-submucosa contain reticular cells, fibroblast, lymphoid cells, plasma cells, granulocytes and interdigitating cells. Few high endothelial venules observed and the cytoplasmic process of these endothelial cells contained small vacuoles equivalent to vesiculo-vacuolar organelles, membrane-bound bodies and vacuolated structures.